CHILDHOOD OBESITY IN KIGALI: EXTENDED THREE-LEVEL APPROACH FOR COST-EFFECTIVE REDUCTION INTERVENTIONS - ASEMOTA, Olukemi Olufunmilola (IJRDO - Journal of Business Management, 2015)
Globally, childhood obesity is becoming a public health concern in developed, developing and medium income countries. Although there are little statistical data on childhood obesity in Rwanda, available evidence indicates that childhood obesity is growing among children and adolescents in Kigali city, due to rapid urbanization and city culture of eating less nutritious energy dense snacks, sedentary lifestyles and little or no physical exercises. Extensive literature search and review coupled with the three-level approach, which entails: screening all children, intervene early for children with body mass index (BMI) greater than 25 but less than 30, and provide intensive intervention for children with BMI greater than 30, were used for this study. The results show some ten-year old children weighed 60kg because of diet and sedentary lifestyles, predisposing them to higher morbidity and mortality. Conclusively, the proposed three-level approach for childhood obesity would drastically reduce multiple risk factors and psycho-social disorders.